THE ROLE OF FEMINIST RESEARCH IN SCHOOL EDUCATION IN THE IMPLEMENTATION OF THE TENDER APPROACH IN SECONDARY SCHOOLS OF GREAT BRITAIN - Lushpay Л.І. (Pedagogy of Higher and Secondary Education, 2022)
The author investigates influence and contribution of feminist research of school system and education on gender approach implementation into educational process of secondary schools in Great Britan.